006 A novel approach in the management of functional neurological disorder in the hyper-acute setting. Issue 9 (12th August 2022) - Shivji, Dhiren; Petrochilos, Panayiota; Balaratnam, Michelle; Lane, Charlie; Nicholson, Clare; See, Isaiah; Alim-Marvasti, Ali-Jesus; Chandratheva, Arvind; Simister, Robert; Haider, Salman
Abstract : Introduction: Functional Neurological Disorder (FND) is common and can lead to multiple emergency department (ED) presentations and unnecessary investigation. Early identification and intervention have been shown to reduce health care costs and re-presentation to acute services by more than 50%1. We created a pilot model to provide early access to a multi-disciplinary FND team for patients assessed by the ED-embedded neurology team (Stroke or Neurology SDEC pathway) to have a new diagnosis of FND. The MDT provided patients with individualised information about FND, pathway navigation, and shown self-management tools. Methods: We reviewed data for all patients seen to date by the pilot service. Results: Since commencement in November 2021, nine patients have been seen by the MDT. All patients were seen within two weeks by a neurophysiotherapist and neuropsychiatrist with neurology support. 6 were female and median age was 41 years. All presented with limb weakness and/or sensory distur- bance. 7 reported prior anxiety or depression. 6 had psychiatric factors, including Emotionally Unstable Personality Disorder and health anxiety. Follow up, 2 of the 9 patients so far demonstrated reduced health anxiety and increased confidence. Conclusion: An acute FND pathway can provide timely intervention and reduce symptoms for new presentations with FND. 1. Stepped care for functional neurological disorder, A new approach to improving outcomes for a common neurological problem in Scotland. Report and Recommendations, NHS Improvement, February 2012